Optimum Selection of Mining Plans for Pillars Containing Interlayers Based on Numerical Simulation. (22nd March 2022) - Hu, Gaojian; Yang, Tianhong
Abstract : A reasonable selection of the pillar mining plan is the key to ensure smooth mining in the goaf group, which plays an important part in safe production. In formulating and optimizing the pillar mining plan, the influence of the ground pressure evolution law should be fully considered. This paper first introduces two mining plans for pillars, and then, numerical simulations were used to analyze the two mining plans from four perspectives such as stress evolution law, stress concentration degree, force state of pillars, and weak marble layers. The results show that the mining plan 1 that retreats from the middle of the ore body to the two wings is the optimal as it can realize sequential mining in high-stress concentration areas at the middle section. This effectively alleviates the stress on the surrounding rock during mining and will not aggravate the collapse of the marble-interbedded area.